2013
DOI: 10.1111/adb.12066
|View full text |Cite
|
Sign up to set email alerts
|

Genetic influences on alcohol use across stages of development:GABRA2and longitudinal trajectories of drunkenness from adolescence to young adulthood

Abstract: Longitudinal analyses allow us to understand how genetic risk unfolds across development, in a way that is not possible with cross-sectional analyses of individuals at different ages. This has received little attention in genetic association analyses. In this study, we test for genetic effects of GABRA2, a gene previously associated with alcohol dependence, on trajectories of drunkenness from age 14 to 25. We use data from 1070 individuals who participated in the prospective sample of the Collaborative Study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 51 publications
3
38
1
Order By: Relevance
“…There is some inconsistency regarding which is the risk allele/haplotype from these yin–yang haplotypes and SNPs within them. For example, for the well-studied polymorphism, rs279858 (see “Methods” for more detail), some studies found that the major (A) allele predicted risk for externalizing-related problems [15, 20, 28]. However, others found that the minor (G) allele predicted risk for externalizing phenotypes such as conduct and alcohol problems in predominantly Caucasian samples [12, 16, 23, 24, 29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some inconsistency regarding which is the risk allele/haplotype from these yin–yang haplotypes and SNPs within them. For example, for the well-studied polymorphism, rs279858 (see “Methods” for more detail), some studies found that the major (A) allele predicted risk for externalizing-related problems [15, 20, 28]. However, others found that the minor (G) allele predicted risk for externalizing phenotypes such as conduct and alcohol problems in predominantly Caucasian samples [12, 16, 23, 24, 29].…”
Section: Introductionmentioning
confidence: 99%
“…First, because stability in problem behaviors might be more genetically influenced [44] while change in symptoms over time might be more environmentally influenced [45], we wanted to ensure that we were not weakening genetic effects by predicting change in symptoms. Second, researchers have also emphasized the importance of evaluating genetic influences on changes in behavior over time, especially during the critical developmental period of adolescence [28]. …”
Section: Introductionmentioning
confidence: 99%
“…It is also known that common genetic influences contribute to a spectrum of correlated externalizing behaviors (Dick et al, 2005, 2008, 2009; Kendler et al, 2003; Krueger et al, 2002; Slutske et al, 1998), and that genetic associations with these behaviors may change across development. For example, variants in the GABRA 2 gene are associated with conduct disorder during childhood, and then alcohol problems beginning in late adolescence through adulthood (Dick et al, 2006, 2013). This suggests that genetic predispositions may manifest differently at different ages, which may be due to environmental changes such as greater autonomy and greater opportunities to express those predispositions.…”
Section: Discussionmentioning
confidence: 99%
“…Belsky et al [58] reported that a multi-locus genetic risk score, derived from the results of meta-analyses for nicotine dependence, was unrelated to initiation of tobacco use but was significantly associated with increased risks for daily tobacco use, more rapid progression from initiation to heavy use, increased risks for the development of nicotine dependence and reduced likelihood of successful cessation. The literature on substance use behaviour trajectories has typically studied behaviour change that occurs between substance use stages, and modelling development and changes in substance use over time has found that GABRA2 is associated with an increase in drunkenness between ages 18–19, suggested to be due to the enhanced independence related to reaching adulthood [85]. Similarly OPRM1 has been found to differentiate those who were light drinkers from those who had progressed to moderate drinking in participants followed-up over 6 years (participants on average aged 14.3 at start of study) [49].…”
Section: Considering the Stage-sequential Nature Of Drug Dependencementioning
confidence: 99%
“…Different environmental influences are also likely to operate at each stage, and research into trajectories suggests that environmental change should be incorporated into analysis [85]. Taking this approach to research is key for gaining a comprehensive understanding of G×E in the development of adolescent substance use, and to reaching meaningful conclusions about opportunities for intervention.…”
Section: Considering the Stage-sequential Nature Of Drug Dependencementioning
confidence: 99%